PELATIHAN EMERGENCY RESPON TINGKATKAN KESIAPSIAGAAN SISWA - Tuwohingide, Yanli Everson; Gobel, Iswanto; Welembuntu, Meistvin (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Health issues occurring in schools must be addressed promptly to prevent the escalation of diseases. The considerable distance between schools and healthcare facilities presents a significant challenge in managing health-related incidents. The geographical remoteness from healthcare facilities, the vulnerability of adolescents to diseases, and the lack of understanding regarding the importance of prevention over treatment were key considerations for the team in selecting an appropriate method for training emergency response among students at Madrasah Aliyah Pettta, Sangihe Island Regency, North Sulawesi Province, Indonesia. The target group was students in grades 10 and 11. Health education was provided to these students, who were gathered at the school, with the materials delivered by facilitators. Following the educational sessions, practical demonstrations of skills that could be employed to manage specific health conditions were conducted. Participants were then allowed to practice these skills independently. The effectiveness of the activity was assessed through a pre- and post-test to evaluate participants’ understanding of the material. The material was well received by the participants, as evidenced by an increase in their knowledge. Before the session, they had only 32% knowledge, but after the health education sessions, it increased to 93%. Students were also able to perform the skills taught independently. The provision of the health equipment was expected to assist the school in managing unforeseen health emergencies during school events or activities. Emergency response training for students significantly enhances both their skills and knowledge. Identifying common health issues in the community is essential, as it allows for the delivery of targeted health education that empowers students to assist their families at home.